Key Technologies of Wavelength Routing for Space-based Information Network - Xin LI; Yongjun LI; Cong PENG; Shanghong ZHAO (天地一体化信息网络)
With the expansion of space exploration scope and the enrichment of exploration means, the number of users carried by space-based information networks has increased rapidly, and the types of services have been continuously updated.As a key technology of optical network, wavelength routing technology is of great signifi cance to improve wavelength utilization and ensure network service quality.Three typical wavelength routing methods of space-based information networks based on multi-service, dynamic characteristics and software defi nition were introduced.And the intelligent wavelength routing technology, hierarchical wavelength routing technology and multipath wavelength routing technology in space-based information networks were studied.The key technologies of wavelength routing in space-based Optical information networks were prospected.